At different methods will cut out research of output of radial saw-timbers - Koshyrets, Svitlana; Gryciuk , Yuriy (Forestry, Forest, Paper and Woodworking Industry, 2024)
The comparative analysis of output of radial saw-timbers is conducted at different methods will cut out logs of coniferous breeds. It is set that will cut out a open-segment-angular method enables to get the greater by volume output of radial saw-timbers than open-segment.